Situated Visualization in Public Spaces: an approach for civic media strategies - dos Santos, André Pinto; Jorge, Liziane de Oliveira; Villaça, Rodolfo da Silva; de Almeida, Marcela Alves (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2024)
Situated visualizations integrate technologies to create data visualization experiences, allowing people to obtain information beyond the computer screen by connecting information to the real world. They can function as decision support systems by facilitating understanding of a phenomenon. In addition, situated visualizations in public spaces promote the democratization of data and information performing as civic media, which are inclusive and collaborative in mobilizing citizens about urban problems. This article presents a practical experiment: an interactive installation that presents data on pedestrian accidents in the Região Metropolitana de Vitória. The installation presents an information panel, a data selector panel, an interactive totem, and a carpet/map.The results show that users had a good experience with the installation, obtaining information interactively and entertainingly. Furthermore, this installation can display data on other urban problems, thus democratizing information. The experiment shows that situated visualization can promote civic action, making citizens aware of urban problems, stimulating reflection, and, potentially, the search for improvements in urban communities.